Medical negligence proceedings in Singapore: Instilling a gentler touch - Dorcas QUEK ANDERSON, (Institutional Knowledge at Singapore Management University, 2021)
Medical malpractice is an area that traverses a wide range of issues in any society – the quality and cost of healthcare, the insurance industry, the cost of litigation, the impact on medical practice and the heightened emotions arising from injuries or even loss of lives. Evidently, the question of compensation for medical malpractice impinges on each of these challenges. Like many countries, Singapore has been grappling with these issues through implementing various reforms in the legal and healthcare sectors. Although compensation has historically been obtained through legal proceedings in the Singapore courts, there is a growing shift towards adopting a much gentler touch to deal with the unique issue of medical malpractice. This article examines the current legal framework for medical negligence in Singapore and the different ways in which the adversarial approach to medical malpractice proceedings is being changed. It concludes with several proposals on how to consolidate and refine the current reforms.